The impact of pre-hospital thrombolytic treatment on re-infarction rates: analysis of the Myocardial Infarction National Audit Project (MINAP). Issue 7 (8th October 2007) - Horne, S; Weston, C; Quinn, T; Hicks, A; Walker, L; Chen, R; Birkhead, J
Abstract : Objective: To examine the frequency and determinants of re-infarction after thrombolytic treatment of ST-elevation myocardial infarction (STEMI). Design: Observational study of national registry. Setting: Emergency ambulance services and admitting hospitals in England and Wales. Patients: 35 356 patients with STEMI given thrombolytic treatment in 2005–6. Main outcome measures: Re-infarction during hospital admission. Results: For 22 391 patients (63.3%) the presence or absence of re-infarction was recorded, and 1460 (6.5%) had re-infarction. Re-infarction rates with in-hospital treatment were similar for reteplase (6.5%) and tenecteplase (6.4%). When the interval from pre-hospital treatment to hospital arrival was greater than 30 minutes re-infarction rates were 12.5% for reteplase, and 11.4% for tenecteplase. Overall, re-infarction rates were higher after pre-hospital treatment with tenecteplase than reteplase (9.6% vs 6.6%, p = 0.005). After multivariate analysis independent predictors of re-infarction for tenecteplase were pre-hospital treatment, OR 1.44 (95% CI 1.21 to 1.71, p<0.001) and weight in the highest quartile compared to the lowest, OR 1.66 (95% CI 1.19 to 2.31, p = 0.003). For reteplase neither factor predicted re-infarction. Bleeding was less common with pre-hospital treatment—overall 1.8% against 3.1%; intracerebral bleeding 0.4% against 0.7%. Conclusion: Pre-hospital treatment with tenecteplase was associated with higher re-infarction rates. Longer intervals from pre-hospital treatment to arrival in hospital were associated with high re-infarction rates for both tenecteplase and reteplase. Differences in the use of adjunctive anti-thrombotic therapy in the two treatment environments may underlie the differences in re-infarction rates and bleeding complications observed between pre-hospital and in-hospital thrombolytic treatment.